2010
DOI: 10.1111/j.1463-1318.2010.02279.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of bacteraemia after argon plasma coagulation in patients with chronic radiation proctocolitis

Abstract: APC is a low-risk procedure regarding bacteraemia and does not warrant prophylactic antibiotic administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…No additional studies were found by hand‐screening of the included articles’ references. Finally, 111 met the criteria . Additional information was kindly provided by the corresponding author of one study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional studies were found by hand‐screening of the included articles’ references. Finally, 111 met the criteria . Additional information was kindly provided by the corresponding author of one study .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 111 Rhodotorula infections studies, 54 (48.6%) reported fungaemias, accounting for 153 patients out of 248 (61.7%) in total . Among patients with fungaemia, 62.8% were male (76 out of 121 cases w.a.d.)…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41][42][43] Some of the older techniques and those for which limited data exist will not be discussed further. Instead, we will address techniques that appear to be more widely used, such as APC.…”
Section: Endoscopic Interventionsmentioning
confidence: 97%
“…79 Another possible complication after APC is bacteremia. 80 In 2011, Lenz et al 80 found a rate of bacteremia of 7% in a small sample of patients undergoing APC.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%